Evaluation Usage of Interactive Quiz Reproductive Systems Based on Usability in Prospective UKMPPD Students (Future Science, 2022)
The use of information technology and interactive multimedia in education is very important. The example of interactive multimedia or e-learning is an interactive quiz. There is multimedia that is easy to use, but sometime it make users confused. High usability of interactive application materials is an important element in ensuring maximum educational impact. This study aims to evaluate the usability, acceptance of interactive quiz media. This research was conducted on 20 student respondents of prospective UKMPPD participants. Interactive quiz media tested using reproductive system materials. Evaluation of interactive quizzes through usability testing with system usability scale (SUS) and user experience questionnaire (UEQ). User acceptance based on SUS is 72 with an acceptability rate in the acceptable category, a grade scale in the